(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The disease Amavata i.e. Rheumatoid arthritis is a challenge for the physician because of its apparent chronicity, incurability, complications, morbidity and crippling nature. About 0.5-1% of the world’s population suffers from Rheumatoid arthritis. Rheumatoid arthritis has generated universal interest among research scholars around the world. Many efforts have been made at this institute and other research centres to study different aspects of Amavata. The present study conducted clinical trials on Amavata. Till date no satisfactory treatment has been available for Amavata disease. The main objective of the treatment of this disease is to provide relief in the form of reduced pain and discomfort, prevention of further disease process, loss of joint function, maintaining productive and active life and above all to restore the vitality of the body (oja) or a good immune status. The disease Amavata, still remains a formidable disease, being capable of producing severe crippling deformities and functional disability. Today’s scenario most of the people affected from this disease specially, old people. In Modern medicine, lesser number of drugs are available along with more side-effects. Also, less improvement and longtime treatment. So, Ayurvedic drugs such as Simhanada guggulu as mentioned in Chakradatta Samhita, Erand taila etc are given a new hope for such a disease along with no side-effects.